Measuring the Capacity to Love: Development of the CTL-Inventory - Kapusta, Nestor D.; Jankowski, Konrad S.; Wolf, Viktoria; Chéron-Le Guludec, Magalie; Lopatka, Madlen; Hammerer, Christopher; Schnieder, Alina; Kealy, David; Ogrodniczuk, John S.; Blüml, Victor (Frontiers in Psychology, 2018)
OBJECTIVE: The individual capacity to love has been linked to various mental health parameters and is considered to be an important outcome parameter of psychotherapeutic treatment. However, empirical examinations of the concept have not been conducted up to now. The aim of this study was to develop a valid and reliable instrument for the assessment of capacity to love (Capacity to Love Inventory, CTL-I) as a trait of personality, which is shown to be related to clinically relevant symptoms and conditions. METHOD: Four independent healthy samples in Austria (n=547, n=174, n=85) and Poland (n=240) were assessed by a prototype of the CTL-I and its final shorter version in a confirmatory factor analysis (CFA). Internal consistency of the total questionnaire and each subscale was assessed by Cronbach alpha. External validity was measured against Beck Depression Inventory (BDI-II-R), Quality of Relationship Inventory (QRI), Sociosexual Orientation Inventory (SOI-R), Pathological Narcissism Inventory (PNI) and Narcissistic Personality Inventory (NPI) according to the theoretical framework of the CTL concept. Further test-retest reliability was assessed. RESULTS: The CFA confirmed 41 items in six dimensions: Interest in the life project of the other, Basic trust, Humility and gratitude, Common ego ideal, Permanence of sexual passion, and Acceptance of loss/jealousy/mourning. The Cronbach alphas of the total CTL-I and its subscales ranged between .67 and .90 and in all samples, suggesting a valid construct. The CTL-I was moderately positively associated with quality of relationship (Support r=.63, Conflict r=-.66, Depth r=.66) and inversely associated with symptoms of depression (r=-.37), pathological narcissism (r=-.29) and promiscuity (r=-.42). The test-retest reliability of the total CTL-I was high with r=.81, suggesting the stability of answers over time. CONCLUSIONS: The proposed 41-item version of the CTL-I is a psychometrically sound and validated instrument measuring six dimensions of the concept of the capacity to love. The reported negative associations with clinically relevant parameters such as depression, pathological narcissism and promiscuity as well as associations with relationship qualities such as conflicts, support and depth warrant its future use in burdened populations including couples in clinical settings.